Screening, identification, and anti-alcoholic and anti-drunken efficacy evaluation of ethanol-degrading lactic acid bacteria - SONG Jia, YU Ping, LIN Xinmei, CHEN Xuejiao, WANG Tingting, PENG Yongzhen (Zhongguo niangzao)
Lactic acid bacteria were isolated from milk pimple (traditional fermented food) samples by traditional culture separation method, and the strains with high ethanol degradation function were screened by ethanol degradation test in vitro, and were identified by morphological observation, physiological and biochemical experiments and molecular biology techniques. Safety evaluation, stress tolerance tests, anti-alcoholic and anti-drunken efficacy tests in mice of screened strain were carried out. The results showed that a strain of Pediococcus acidilactici RH2712 with high ethanol degradation rate (13.38%) and strong ethanol tolerance (tolerant volume fraction 12% ethanol) was screened and identified. The strain was sensitive to antibiotics, such as ampicillin, penicillin, imipenem and chloromycetin, but with safe hemolysis. It had strong tolerance to acid and bile salt, and the logarithm value of living bacteria was almost unchanged under the condition of pH 3.0, and the delay time was 2 h. After cultured for 4 h under 1.5% bile salt content, the logarithm value of living bacteria reached 8.72, and the delay time was only 0.5 h. Under the condition of artificial simulated gastric juice, the logarithm value of living bacteria could reach 7.14 after 3 h. P. acidilactici RH2712 showed obvious anti-alcoholic and anti-drunken efficacy in mice, and the anti-alcoholic function was stronger than metadoxine when the number of living bacteria was 1×108-1×109 CFU/ml.